The Optimal Minimum Wage with Regulatory Uncertainty - John Bennett; Ioana Chioveanu (Institute for the Study of Labor (IZA), 2015)
For two different regulatory standards, we examine the optimal minimum wage in a competitive labour market when the government is uncertain about supply and demand. Solutions are related to underlying supply and demand conditions, and the extent of uncertainty and of rationing efficiency. We show that regulatory uncertainty does not diminish the rationale for intervention, but may require a low minimum wage that may not bind. With expected earnings-maximization, greater uncertainty widens the range of parameter values for which a minimum wage should be set. With expected worker surplus-maximization and sufficiently efficient rationing, a minimum wage should always be set.
Keywords: J38; J31; 330; minimum wage; uncertainty; worker surplus